Work in Progress: Native language consistency effect on learners' introduction to block-based instructional technologies (2021)
This lightning talk discusses how cultural factors such as learners' native language may impact the understanding of CS concepts. We present findings from an evaluation we conducted with adult participants, Native-English speakers and Bilingual-Hispanics with no prior coding experience, performing tasks in a conventional block-based programming platform: Scratch.